The proximity of the N- and C- termini of bovine knob domains enable engineering of target specificity into polypeptide chains. Issue 1 (31st December 2022) - Hawkins, Alice; Joyce, Callum; Brady, Kevin; Hold, Adam; Smith, Alan; Knight, Michael; Howard, Conor; van den Elsen, Jean; Lawson, Alastair D.G.; Macpherson, Alex
ABSTRACT: Cysteine-rich knob domains can be isolated from the ultralong heavy-chain complementarity-determining region (CDR) 3, which are unique to a subset of bovine antibodies, to create antibody fragments of 4 kDa. Advantageously, the N- and C- termini of these small binding domains are in close proximity, and we propose that this may offer a practical route to engineer extrinsic binding specificity into proteins. To test this, we transplanted knob domains into various loops of rat serum albumin, targeting sites that were distal to the interface with the neonatal Fc receptor. Using knob domains raised against the clinically validated drug target complement component C5, we produced potent inhibitors, which exhibit an extended plasma half-life in vivo via attenuated renal clearance and neonatal Fc receptor-mediated avoidance of lysosomal catabolism. The same approach was also used to modify a Camelid VHH, targeting a framework loop situated at the opposing end of the domain to the CDRs, to produce a small, single-chain bispecific antibody and a dual inhibitor of Complement C3 and C5. This study presents new protein inhibitors of the complement cascade and demonstrates a broadly applicable method to engineer target specificity within polypeptide chains, using bovine knob domains.